IMPROVING THE QUALITY OF RESEARCH AND PUBLICATIONS IN SCOPUS JOURNALS FOR LECTURERS AND STUDENTS - Navel Oktaviandy Mangelep; Patricia V. Runtu; Fricy O. Rumintjap; Deysti T. Tarusu; Anita Nisa Kambey (Universitas Pahlawan Tuanku Tambusai, 2025)
The community service activity with the title